2013
DOI: 10.1016/j.ijid.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of hepatocellular carcinoma mortality rates among hepatitis B virus-infected renal transplant recipients, with supplemental analyses of liver failure and all-cause mortality

Abstract: Mortality due to HCC was increased in low and intermediate seroprevalence areas, but the evidence was inconclusive for high seroprevalence areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The author compared the HCC mortality in HBV positive kidney transplant recipients with that of HBV positive general populations, and found that the HCC mortality rate was increased in low and intermediate seroprevalence areas, but inconclusive in high seroprevalence areas. 18 Different surveillance programs may contribute to differences in HCC mortality in various studies. The HCC mortality rate in our HBV positive kidney transplant recipients was 263/100,000 person-years, which was comparable with that of the HBV positive general population in high seroprevalence areas such as Taiwan (283.5/100,000 personyears).…”
Section: Discussionmentioning
confidence: 99%
“…The author compared the HCC mortality in HBV positive kidney transplant recipients with that of HBV positive general populations, and found that the HCC mortality rate was increased in low and intermediate seroprevalence areas, but inconclusive in high seroprevalence areas. 18 Different surveillance programs may contribute to differences in HCC mortality in various studies. The HCC mortality rate in our HBV positive kidney transplant recipients was 263/100,000 person-years, which was comparable with that of the HBV positive general population in high seroprevalence areas such as Taiwan (283.5/100,000 personyears).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigation into novel methods to improve the treatment and survival of liver cancer patients is essential. The pathogenesis of liver cancer is complex, and studies have demonstrated that uncontrolled proliferation, various ion disorders and resistance to apoptosis are key features of this process ( 4 ). However, the exact mechanisms of pathogenesis are unclear, particularly that of apoptosis resistance.…”
Section: Introductionmentioning
confidence: 99%